STEAP4 Inhibits HIF-1α/PKM2 Signaling and Reduces High Glucose-Induced Apoptosis of Retinal Vascular Endothelial Cells - Liu L; Xu H; Zhao H; Jiang C (Diabetes, Metabolic Syndrome and Obesity, 2020)
Lei Liu,1 Hui Xu,1 Hongyu Zhao,2 Chunying Jiang1 1Department of Ophthalmology, The First Hospital of Jilin University, Changchun 130021, People’s Republic of China; 2Department of Radiation Oncology, China-Japan Union Hospital of Jilin University, Changchun 130033, People’s Republic of ChinaCorrespondence: Chunying JiangDepartment of Ophthalmology, The First Hospital of Jilin University, No. 71 Xinmin Street, Changchun 130021, People’s Republic of ChinaEmail jiangchunying2020@163.comBackground: Diabetic retinopathy (DR) is a vascular lesion induced by high glucose. STEAP4 is an indispensable membrane protein, which is closely related to hyperglycemic-induced cell inflammation and injury, while STEPT4 has not been studied in hyperglycemic-induced retinal vascular endothelial cell injury.Methods: The expression of STEAP4 was detected by RT-qPCR and Western blot. CCK-8 was used to detect cell survival. STEAP4 was overexpressed by cell transfection. The expressions of cytokines TNF-α, IL-1, IL-6, ICAM-1, MDA, SOD and ROS were detected by ELISA. Cell apoptosis was detected by flow cytometry. The expressions of proteins associated with cell damage VEGF, KLF2, eNOS and apoptosis-related proteins Bax, cleaved caspase3 and Bcl2 were detected by Western blot. Finally, the expressions of HIFα and PKM2 were detected by immunofluorescence and Western blot.Results: The expression of STEAP4 in hyperglycemic-induced retinal vascular endothelial cells (HRCECs) decreased gradually. Overexpression of STEAP4 reduced inflammation and apoptosis of HRCECs and improved dysfunction of them. Meanwhile, overexpression of steap4 inhibited the expression of HIF-1α/PKM2 signal.Conclusion: STEAP4 can be a potential therapeutic target for diabetic retinopathy by inhibiting HIF1/PKM2 signaling to reduce hyperglycemic-induced retinal cell apoptosis.Keywords: diabetic retinopathy, STEAP4, HIF-1α/PKM2, HG-induced retinal vascular endothelial cells